Jurnal Strategi Pemberdayaan Masyarakat dalam Pengelolaan Lingkungan Berbasis Partisipatif di Kota Metro - saputra, pindo riski (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2025)
effective approach to sustainable environmental management. This study explores empowerment strategies in Metro City, Lampung, by integrating an analysis of factual environmental conditions such as daily waste generation, irrigation pollution, and the shortage of green open spaces. A descriptive qualitative method was employed through literature review, analysis of local government documents, media reports, and academic research. The findings indicate that effective empowerment strategies involve strengthening local capacities, active community participation in waste bank management, adherence to the STBM (Community-Based Total Sanitation) framework, and multi-stakeholder collaboration. The main obstacles include limited funding, weak inter-agency coordination, and low public awareness. The study recommends enhancing policy support, providing incentives, and establishing inclusive mechanisms for participatory-based sustainable development.